2021
DOI: 10.1002/pssa.202100461
|View full text |Cite
|
Sign up to set email alerts
|

Back‐Contacted Carrier Injection for Scalable GaN Light Emitters

Abstract: It has recently been proposed that back‐contacted III–V light‐emitting diodes (LEDs) could offer improved current spreading as compared to conventional mesa or double side contacted structures. This has inspired also experimental efforts to realize such structures, but fabrication methods for them have not yet been fully established. Herein, the use of unintentionally doped and partially carrier‐selective contacts (SC) is studied to realize back‐contacted indium gallium nitride (InGaN) LEDs. The sharp electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…The active device area used to calculate the average current densities through the devices is defined as the area of the p-mesa including the contact pad (1000 µm × 350 µm) and the area of the fingers calculated as W F × N × L F , which is slightly different for each device. Overall, the lateral dimensions of the studied devices here are similar to the recently reported GaN-based DDCT-LEDs [22].…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The active device area used to calculate the average current densities through the devices is defined as the area of the p-mesa including the contact pad (1000 µm × 350 µm) and the area of the fingers calculated as W F × N × L F , which is slightly different for each device. Overall, the lateral dimensions of the studied devices here are similar to the recently reported GaN-based DDCT-LEDs [22].…”
Section: Methodssupporting
confidence: 85%
“…Fabrication of compound semiconductor-based DDCT devices is not established due to the unconventional device structures and lack of appropriate lateral doping techniques. So far, experimental studies on DDCT-LEDs have focused merely on GaN devices [10], [21], [22], [23], [24], while GaAs devices have been considered only theoretically [7], [8], [9]. The first report of GaN-based DDCT-LEDs by Riuttanen et al [10] demonstrated the fundamental principle of DDCT by injecting holes into AR through an n-GaN layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation